1987
DOI: 10.1177/036354658701500403
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of Achilles tendinitis

Abstract: Inflammation of the Achilles tendon and its contiguous structures is one of the most common overuse problems seen in runners. There are actually several etiologies. Involvement of the tendon itself is secondary to areas of mucinoid or fibrotic degeneration, or may be a result of a partial rupture. The sheath (or mesotenon) may also become chronically inflammed. Retrocalcaneal bursitis seems to be a separate entity with hypertrophy and fibrosis of the bursa usually occurring in conjunction with a prominent post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(142 citation statements)
references
References 10 publications
0
137
0
5
Order By: Relevance
“…Mucoid degeneration has been reported in the Achilles tendon in both ruptures (Amer et al 1959, Kannus andJdzsa 1991) and tendinosis, mostly among athletes (Clancy et al 1976, Puddu et al 1976, Merkel et al 1982, Schepsis and Leach 1987, Nelen et al 1989.…”
Section: Tendon Pathology In Long-standing Achillodynia Biopsy Findinmentioning
confidence: 99%
“…Mucoid degeneration has been reported in the Achilles tendon in both ruptures (Amer et al 1959, Kannus andJdzsa 1991) and tendinosis, mostly among athletes (Clancy et al 1976, Puddu et al 1976, Merkel et al 1982, Schepsis and Leach 1987, Nelen et al 1989.…”
Section: Tendon Pathology In Long-standing Achillodynia Biopsy Findinmentioning
confidence: 99%
“…Satisfactory results have been reported in approximately 80 to 90 per cent of the cases (14)(15)(16). However, in a recent series of patients with chronic Achilles tendinopathy treated surgically it was reported that non-athletic patients experience more prolonged recovery, more complications and are at greater risk for further surgery than athletic patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, operative treatment should be considered when a comprehensive nonoperative treatment program of several months' duration has failed and the patient is not willing to alter or abandon the precipitating sports activity [39]. Surgical treatment is required in about 25% of athletes with Achilles tendon overuse injuries [41].…”
Section: Treatmentmentioning
confidence: 99%